Information System for the Development of Web-Based Fixed Asset Modules at PT. Prima Solusi Computindo - Andika, Ferry; Nuriantoro, Fajar Rizki; Putra, Andreas Bayu; Haryono, Wasis (SAN Scientific, 2025)
Prima Solusi Computindo (Radsoft) faces challenges in managing fixed assets, resulting in inefficiencies due to manual and non-integrated record-keeping processes. This study aims to design and implement a web-based information system for fixed asset management to enhance efficiency and accuracy. This system was developed using HTML, CSS, Javascript, SQL database, and the C# framework. The research utilizes the Waterfall development model, encompassing requirements analysis, system design, implementation, and testing phases. The results indicate that the developed system effectively integrates asset management processes, including record-keeping, depreciation tracking, and reporting. This integration simplifies the management team's decision-making regarding asset utilization. Additionally, the web-based system enables real-time access across departments, improving transparency and data accuracy. As a recommendation, the company should provide training for system users to maximize the features available. Future developments include integrating the system with other modules, such as accounting and inventory, to enhance its overall functionality.